EVALUASI PROGRAM LATIHAN ATLETIK PADA ATLET LARI JARAK JAUH - fatimah Zahra; Irfandi Tarigan; Joy Immanuel; Bina Pratama (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2025)
This study aims to evaluate the athletic training program for long-distance runners to determine the effectiveness of its implementation in improving athlete performance. The research method used is descriptive evaluative with a mixed methods approach. The research subjects consisted of long-distance running athletes who are members of a club or team. Data collection techniques were carried out through observation, interviews, documentation, and physical fitness tests such as endurance and VO2max. Data analysis employed the CIPP (Context, Input, Process, Product) evaluation model. The results showed that the training program has been implemented fairly well; however, several weaknesses were identified, including the lack of training variation, suboptimal application of periodization principles, and limitations in the use of performance measurement tools. Nevertheless, the program was able to improve athletes’ endurance, although the improvement was not evenly distributed among all athletes. Therefore, continuous evaluation and more systematic development of training programs are needed to optimize athlete performance.